Effect of climatic factors like rainfall, humidity and temperature on the dengue cases in the metropolitan city of Maharashtra - Pol, Sujata Shirish; Rajderkar, Shekhar S.; Dhabekar, Pallavi D.; Bansode Gokhe, Seema S. (International Journal Of Community Medicine And Public Health, 2021)
Background: Climatic factors may influence the dengue cases in the given geographical area indicating the need of research on it. The research in India, especially Maharashtra is however scarce. Thus a study on climatic factors and dengue cases was planned in metropolitan city of Maharashtra. Objective was to study the effect of climatic factors like rainfall, humidity and temperature on the dengue incidence. Methods: Retrospective study design was commissioned at tertiary care hospital in the city. The reported DF/DHF cases during January 2009 to December 2018 were mobilised from Integrated Disease Surveillance Project (IDSP) of Epidemiology cell, Mumbai. Climate records were gathered from meteorology department of the city. Data were entered on the Excel sheet. The analysis was done with SPSS version 22.0. Results: The dengue incidence was high in monsoon and post monsoon season. Both rainfall and humidity were positively and temperature was negatively associated with dengue incidence. Conclusions: Climatic factors are the best predictors of dengue cases in near future. Weather factors based early warning systems may be incorporated in the routine surveillance system for dengue for preventing the epidemic.